2003
DOI: 10.4049/jimmunol.171.7.3718
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Avidity and Specificity on the Antiviral Efficiency of HIV-1-Specific CTL

Abstract: Although CD8+ CTLs are presumed to be an important mediator of protective immunity in HIV-1 infection, the factors that determine CTL antiviral efficiency are poorly understood. Two factors that have been proposed to influence CTL antiviral function are antigenic avidity and epitope specificity. In this study we evaluate these by examining the activity of HIV-1-specific CTL against acutely infected cells. The ability of CTL to kill infected cells is variable and depends more on epitope specificity than functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
68
2
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 39 publications
14
68
2
1
Order By: Relevance
“…5) despite its modest functional avidity and tetramer binding activity (Table 1). This finding appears to be consistent with the recently reported study demonstrating that epitope specificity of CTL, rather than functional avidity of CTL, is a key factor in the ability of CTL to control HIV replication, and that the process of epitope presentation on HIV-infected cells greatly influences CTL efficiency in vivo [29].…”
Section: Antiviral Replication Activity Of Tcr-transduced Cd8 T Cellssupporting
confidence: 81%
“…5) despite its modest functional avidity and tetramer binding activity (Table 1). This finding appears to be consistent with the recently reported study demonstrating that epitope specificity of CTL, rather than functional avidity of CTL, is a key factor in the ability of CTL to control HIV replication, and that the process of epitope presentation on HIV-infected cells greatly influences CTL efficiency in vivo [29].…”
Section: Antiviral Replication Activity Of Tcr-transduced Cd8 T Cellssupporting
confidence: 81%
“…This was not due to loss of viral replication limiting mutation, because the presence of p24 antigen all in the cultures demonstrated ongoing virion production in the presence of CTL, and escape mutation in the targeted non-Nef protein could be observed in some of the mixed CTL cultures (Table 1 and data not shown). Furthermore, this phenomenon was not explained by lesser recognition of infected cells by Nef-specific CTL compared to the Gag-and RT-specific CTL, as indicated by our previous observations that Nefspecific CTL tend to have far greater antiviral activity than Gag-and RT-specific CTL [29,30], and that RTspecific CTL (the IV9-specific CTL clones tested here) often have relatively weak antiviral activities [25,26]. These data, therefore, indicated that the presence of non-Nef-specific CTL add an important functional constraint that limits the ability of HIV-1 to escape from Nef-specific CTL through disruption of Nef.…”
Section: Resultsmentioning
confidence: 60%
“…TRBV7 structural avidity was assessed by a tetramer off-rate assay similar to recently published methods (37). Recent findings have indicated high structural avidity as a beneficial characteristic of HIV specific CTL (5,(37)(38)(39)(40), as well as convergent evolution of epitope-specific responses in murine models and human influenza studies (41)(42)(43). These data suggest a beneficial role of common TRBV usage against conserved epitopes, perhaps as a result of greater functional capacity.…”
Section: Discussionmentioning
confidence: 99%